(untitled) (International Journal of Engineering and Computer Science, 2018)
Vehicle-to-vehicle (V2V) communication holds a promise to revolutionize road transport operations proposed in vehicular communications as an element of Intelligent Transportation System (ITS). However, the vehicular communication channel suffers from low SNR arising from shadowing, multi-path fading and Doppler shift which degrade detection performance by increasing BER. MIMO techniques improvising diversity gain have been proposed as a mitigation factor to enhance detection. In this paper it is empirically determined that for given processing algorithm BER performance is linearly related to diversity order of the system. Simulations results indicate that detection performance increases with diversity order for a given processing algorithm dependent on the power loading algorithm.